2020
DOI: 10.1111/anae.15281
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative COVID‐19 infection in urgent elective surgery during a pandemic surge period: a retrospective observational cohort study

Abstract: Summary Maintaining safe elective surgical activity during the global coronavirus disease 2019 (COVID‐19) pandemic is challenging and it is not clear how COVID‐19 may impact peri‐operative morbidity and mortality in this population. Therefore, adaptations to normal care pathways are required. Here, we establish if implementation of a bespoke peri‐operative care bundle for urgent elective surgery during a pandemic surge period can deliver a low COVID‐19‐associated complication profile. We present a single‐centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
3
19
0
5
Order By: Relevance
“…Elective surgery after SARS-CoV-2 infection must be safe for staff, other patients and the public [16][17][18][19]. Therefore, adherence to self-isolation guidelines is imperative.…”
Section: Protection Of Othersmentioning
confidence: 99%
“…Elective surgery after SARS-CoV-2 infection must be safe for staff, other patients and the public [16][17][18][19]. Therefore, adherence to self-isolation guidelines is imperative.…”
Section: Protection Of Othersmentioning
confidence: 99%
“…Kane et al demonstrated that low rates of COVID-19 infection and mortality in the elective surgical population could be achieved by using a targeted care bundle. 34 Modifications were suggested at every stage of the perioperative pathway in order to protect both staff and patients from the risks of COVID-19. 35 Important decisions surrounding surgeries had to be implemented quickly and were often based on day-to-day experiences and reflected the rapidly evolving nature of the situation and the associated evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are in line with many other similar studies in various health care centers. 11,12,17 Research comparing the availability of a COVID-19-free operation route with the unavailability of a COVID-19free operating route found that the post-operative patient SARS-CoV-2 infection rate was lower level in the COVID-19-free operation route. 12,18,19 It should be noted that COVID-19 infection without a COVID-19free surgical route in post-operative patients is around 5% with a mortality rate of 25%.…”
Section: Discussionmentioning
confidence: 99%